Factors Affecting the Comprehension of Outpatients Receiving Cancer Chemotherapy - Nishibe-Toyosato, Seira; Ando, Yosuke; Nakasuji, Nayu; Hayashi, Takahiro; Ito, Kaori; Matsuda, Hidezo; Tsujii, Naho; Tsuge, Masahiro; Imaizumi, Kazuyoshi; Kawada, Kenji; Yamada, Shigeki (Biological & pharmaceutical bulletin, 2023)
Pharmaceutical consultation targeting outpatients at the Fujita Health University Hospital (Japan) provides support to patients undergoing anticancer drug treatment. This study aimed to explore factors that affect the comprehension of cancer chemotherapy among outpatients who received cancer treatment at our hospital. A questionnaire survey was conducted, and comprehension was scored on a scale of 1–5 (1, no comprehension; 5, full comprehension). When factors other than age and sex [the influence of which on comprehension has been reported in previous reports] were noted, differences in comprehension between the questionnaire items were comparatively analyzed according to the presence/absence of the relevant factors. Overall, 536 patients were included. Age (<70 years) and pharmacist interventions were identified as factors contributing to a comprehension score. The levels of comprehension regarding the name of the cancer chemotherapy, content/schedule of the treatment, purposes of the prescribed drugs, and objectives of blood tests were significantly higher in the group that received the pharmaceutical interventions; conversely, the level of comprehension for the self-management of adverse events was significantly lower in this group than in the group that did not receive any pharmaceutical interventions. Age and interventions by the pharmacist affected the comprehension of cancer chemotherapy by patients.